Assessing the integration potential of new energy in river basin clean energy corridors considering energy-power coupled complementary operation modes. (1st December 2021) - Zhang, Juntao; Cheng, Chuntian; Yu, Shen; Wu, Xinyu; Su, Huaying
Highlights: The effective complementary operation mode and the new energy's optimal capacity configuration of Beipan river basin clean energy corridor were determined. Integrating new energy into the existing large hydropower bases will change the inter-seasonal distribution of water and electricity of hydropower stations. In the wet year, the ability of hydropower to compensate variable new energy will decline. The capacity of power transmission channels will limit the actual deployment level of the theoretical maximum integration potential of new energy. Abstract: Operating new energy (wind and solar) complementarily with the existing hydropower stations is a promising way for efficient accommodation of utility-scale new energy. China plans to build a batch of river basin hydro–wind–solar clean energy corridors (RBCECs) by integrating new energy into the existing large hydropower bases. This paper proposes a universal method to determine the effective complementary operation mode and the optimal capacity configuration of new energy for RBCECs. First, the energy–power coupled complementary operation modes are proposed to fully tap the hydropower flexibility, compensating the variable new energy. Then, an optimization model framework is constructed to determine the optimal capacity configuration of new energy for RBCECs; the model framework can simulate the 8760–hour–time–series operation of hydro–wind–solar hybrid system. Moreover, the proposed operation modes can be respectively plugged into the model framework to calculate the corresponding optimal capacity configuration of new energy for RBCECs. The Beipan RBCEC in China, is selected as a case study, and its effective complementary operation mode and the optimal capacity configuration of new energy are determined. Results also indicate that (1) integrating new energy into hydropower system will change the inter-seasonal distribution of water and electricity of the hydropower stations; (2) the ability of hydropower stations to compensate variable new energy will be affected by runoff; (3) the theoretical maximal integration potential of new energy in a RBCEC will be affected by the installed hydropower capacity, reservoir storage, and complementary operation modes; but the actual deployment level of the theoretical maximum integration potential will be affected by the capacity of power transmission channels.